Prime Real Estate: Metals, Cofactors and MICOS - Medlock, Amy E.; Hixon, J. Catrice; Bhuiyan, Tawhid; Cobine, Paul A. (Frontiers in Cell and Developmental Biology, 2022)
Metals are key elements for the survival and normal development of humans but can also be toxic to cells when mishandled. In fact, even mild disruption of metal homeostasis causes a wide array of disorders. Many of the metals essential to normal physiology are required in mitochondria for enzymatic activities and for the formation of essential cofactors. Copper is required as a cofactor in the terminal electron transport chain complex cytochrome c oxidase, iron is required for the for the formation of iron-sulfur (Fe-S) clusters and heme, manganese is required for the prevention of oxidative stress production, and these are only a few examples of the critical roles that mitochondrial metals play. Even though the targets of these metals are known, we are still identifying transporters, investigating the roles of known transporters, and defining regulators of the transport process. Mitochondria are dynamic organelles whose content, structure and localization within the cell vary in different tissues and organisms. Our knowledge of the impact that alterations in mitochondrial physiology have on metal content and utilization in these organelles is very limited. The rates of fission and fusion, the ultrastructure of the organelle and rates of mitophagy can all affect metal homeostasis and cofactor assembly. This review will focus of the emerging areas of overlap between metal homeostasis, cofactor assembly and the mitochondrial contact site and cristae organizing system (MICOS) that mediates multiple aspects of mitochondrial physiology. Importantly the MICOS complexes may allow for localization and organization of complexes not only involved in cristae formation and contact between the inner and outer mitochondrial membranes but also acts as hub for metal-related proteins to work in concert in cofactor assembly and homeostasis.